Antipodean theory for educational research. Issue 1 (1st January 2017) - Stewart, Georgina; Arndt, Sonja; Besley, Tina; Devine, Nesta; Forster, Daniella J.; Gibbons, Andrew; Grierson, Elizabeth; Jackson, Liz; Jandrić, Petar; Locke, Kirsten; Peters, Michael A.; Tesar, Marek
ABSTRACT: This article results from a collaborative investigation into Antipodean theory in education by members of the Editors' Collective (www.editorscollective.org.nz ). The Prologue contains a brief personal account of the South Project (www.southernperspectives.net ), as an example of the contemporary projects and activities falling under the banner of 'Antipodean' ways of working and thinking. The Introduction briefly reviews the history of (mainly Western) ideas about the Antipodes, from classical Greek philosophy through to the contemporary globalised era. This is followed by a synopsis of the motivations, purposes and benefits of Antipodean theory, with more detailed examinations of equality, indigeneity, replication and creation as some of its central elements. We consider the role of Antipodean thinking as a located critical theory for education, and a way to defend our aspirations for equality and social justice against the incursions of neoliberalism, today and in the future.